Insights on purchase intention of mutton shashlik - A survey of Chinese consumers based on fsQCA - Guanhua Cai; Che Shen; Xinnan Wu; Meiqi Ding; Ting Zhao; Yutong Li; Bo Wang; Dengyong Liu (Future Foods)
Various factors influence the purchases of meat products by consumers, and their final purchasing behavior has a temporal and logical relationship with their willingness to buy. Such willingness is an effective indicator of purchasing behavior. In this study, sensory appeal, brand loyalty, price, consumer reviews, consumer preferences, and the personal characteristics of consumers (e.g., gender, age, and income) were selected as the antecedent variables. Data from 5,981 consumers were collected through an online questionnaire. The path configurations that caused consumers to have high and low purchase intentions for mutton shashliks were analyzed using fuzzy set qualitative comparative analysis (fsQCA). The major causes that lead consumers to the two choices of purchasing or not purchasing were identified. The findings show that there is a causal asymmetric relationship between customers' desire to purchase meat items and the factors influencing them. As a multifaceted outcome variable, consumer preference traits and cost are the primary determinants of the high purchase intention to buy mutton shashlik, with income and sensory appeal having a lesser effect. Furthermore, factors such as brand loyalty, consumer reviews, gender, and age worked in conjunction with the main factors that influenced or hindered consumers' purchase intentions.